2020
DOI: 10.1016/j.jmig.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Laparoscopic Ovarian Drilling for Clomiphene Citrate-resistant Patients with Polycystic Ovary Syndrome and Infertility: A Meta-analysis

Abstract: Register in February 2019. Methods of Study Selection: Randomized controlled trials (RCTs) evaluating LOD for patients with clomiphene citrateresistant polycystic ovary syndrome and infertility and reporting reproductive outcomes, surgical complications, serum indexes, menses resumption, and ultrasound results were included. Quality and risk of bias were evaluated by 2 authors, respectively. Tabulation, Integration, and Results: A total of 20 RCTs with 1615 patients were included. Evaluation of the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The standard number and/or depth of the perforation or dose and/or the duration of energy sources applied to the ovary to maximize the therapeutic effects remain controversial [92,93]. Most studies propose the use of three to ten punctures for a single ovary and a power setting of 200-300 watts (W) for 2-4 s [27,28,39,46,52,61,88]. Our suggestion is that the number of punctures should be tailored to the individual ovary in each woman with PCOS depending on the ovarian size [94,95].…”
Section: How Many Punctures Are Needed During the Laparoscopic Ovariamentioning
confidence: 99%
See 4 more Smart Citations
“…The standard number and/or depth of the perforation or dose and/or the duration of energy sources applied to the ovary to maximize the therapeutic effects remain controversial [92,93]. Most studies propose the use of three to ten punctures for a single ovary and a power setting of 200-300 watts (W) for 2-4 s [27,28,39,46,52,61,88]. Our suggestion is that the number of punctures should be tailored to the individual ovary in each woman with PCOS depending on the ovarian size [94,95].…”
Section: How Many Punctures Are Needed During the Laparoscopic Ovariamentioning
confidence: 99%
“…LOD may induce overall spontaneous ovulation and pregnancy rates of 30-90% and 13-88% [1,21,28,39,51,60,61,111]. An earlier review showed that there is no statistically significant difference in the ovulation rates following LOD using electrocoagulation and a laser (83% vs. 77.5%; OR 1.4; 95% CI 0.9-2.1) [111].…”
Section: Ovulation and Pregnancy Rates After Laparoscopic Ovarian Drimentioning
confidence: 99%
See 3 more Smart Citations